PERTUMBUHAN SEMAI Rhizophora mucronata PADA SALURAN TAMBAK WANAMINA DENGAN LEBAR YANG BERBEDA - Afiyatul Aini; Rini Budi Hastuti; Endah Dwi Hastuti (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2016)
The expansion of the aquaculture area causes reduction of mangrove ecosystems. Silvofishery combines fisponds and mangrove planting. Rhizophora mucronata often select for rehabilitation of mangrove forests. This research aims to know growth differences of Rhizophora mucronata in the ducts of silvofishery and variation width range of ducts. This research was carried out from the basic of Random Design Group (RAK) used three treatments which each of treatment was repeated 3 times. The treatments were the variation width of the ducts (R): R1 = R2 = 1 m, 2 m and R3 = 3 m. Growth data was analyzed using statistical approach, The Analysis of Variance (ANOVA). The results of the analysis observational during two months research of Rhizophora mucronata showed that the height and diameter growth of each width of duct (1 m, 2 m, 3 m) wasn't significantly different, but there was a growth tendency in height and diameter of Rhizophora mucronata. Mangrove within 3 m width of duct has best growth condition compared with the others. Plant Branch wasn't grown and foliages were grown partially. Key words: Growth, Rhizophora mucronata, Mangrove, Silvofishery.